Global Trends in the Incidence and Primary Causes of Femoral Fractures, Excluding Femoral Neck Fractures: A Global Epidemiological Study - Fu F; Liu B; Pu H; Wang Y; Zhang P; Wei S; Gu H; Zhang Q; Ye H (Risk Management and Healthcare Policy)
Fanyu Fu,1,* Bo Liu,2,* Haifang Pu,3 Yuebin Wang,3 Pengfei Zhang,1 Song Wei,1 Hao Gu,1 Qian Zhang,4 Hengli Ye5 1College of Physical Education and Health Science, Yibin University, Yibin, 644000, People’s Republic of China; 2Department of Orthopedics and Traumatology, Yibin Hospital of Traditional Chinese Medicine, Yibin, 644600, People’s Republic of China; 3Department of Pain, the Second People’s Hospital of Yibin, Yibin, 644000, People’s Republic of China; 4Department of Rheumatology and Immunology, Taizhou First People’s Hospital, Taizhou, 318020, People’s Republic of China; 5Department of Orthopaedics and Joints, Huangyan Hospital of Traditional Chinese Medicine, Taizhou, 318020, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hengli Ye, Huangyan Hospital of Traditional Chinese Medicine, 83 Century Avenue, Xinqian Street, Huangyan District, Taizhou, 318020, China, Email dryehengli@126.comPurpose: Fractures pose a significant global health challenge, with varying incidence trends and causes across demographics and regions. This study aims to analyze global patterns in the incidence and primary causes of femoral shaft fractures.Methods: Data from the Global Burden of Disease database were analyzed for femoral fractures (excluding femoral neck fractures) by age, gender, and socio-demographic index regions. The estimated annual percentage change (EAPC) was calculated to assess trends in the incidence of femoral shaft fractures.Results: Global femoral fracture cases increased from 8,559,886 in 1990 to 11,566,429 in 2021, a rise of 35.12%. However, the incidence rate dropped from 160.49 to 146.57 per 100,000 (EAPC: − 0.35). Males consistently had higher rates, reaching 155.53 per 100,000 in 2021. The 15– 49 age group recorded the most cases, while individuals aged 75 and older saw the largest rise in incidence, from 445.91 to 603.32 per 100,000. In 2021, Slovenia (616.1 per 100,000), Croatia (568.51 per 100,000), and Czechia (434.77 per 100,000) reported the highest rates, while Malawi, Kiribati, and Liberia had the lowest (< 63 per 100,000). Leading causes were mechanical forces, motor vehicle injuries, and pedestrian injuries, with notable regional disparities.Conclusion: Although the global incidence rate of femoral shaft fractures has declined, it has risen significantly among older adults, increasing their burden. Understanding regional variations in causes is crucial for developing targeted public health interventions to address this growing issue. Keywords: femoral shaft fractures, global epidemiology, incidence, injury